Evaluation of 4H-4-chromenone derivatives as inhibitors of protein kinase CK2 - Prykhodko, A.O.; Yakovenko, O.Ya.; Golub, A.G.; Bdzhola, V.G.; Yarmoluk, S.M. (Біополімери і клітина, 2005)
Protein kinase CK2 (Casein Kinase 2) is a ubiquitous serine/threonine protein kinase involved in various cell signal transduction pathways. Thus, CK2 is a new perspective target for anticancer drugs. The receptor-based virtual screening of 2000 compounds from combinatorial library of 4H-4-chromenones has been carried out in search for CK2-inhibitors. 90 compounds have been chosen for biological testing based on the score values calculated by DOCK 4.0 software. It has been revealed, that 3-(4-chloro-3,5-dimethylphenoxy)-7-(4-methoxyphenylcarbonyloxy)-4-oxo-4H-chromene (12) and 7-(4-fluorophenylcarbonyloxy)-4-oxo-3-(4-phenylphenoxy)-4H-chromene (14) inhibit CK2 activity with IC50= 18.8 mM and IC50=22.4 mM, respectively. Протеїнкіназа СК2 є убіквітальною багатосубстратною кіназою, що залучена до багатьох сигнальних шляхах клітинного росту та проліферації. СК2 кіназа розглядається як перспективна мішень для створення протиракових ліків. Для пошуку інгібіторів протеїнкінази СК2 нами проведено комп'ютерний рецептор-орієнтований віртуальний скринінг 2000 сполук комбінаторної бібліотеки 4Н-4-хроменону. На основі розрахованих програмою DOCK 4.0 оціночних показників вільної енергії взаємодії відібрано 90 сполук для біологічного тестування. Знайдено, що дві сполуки пригнічують активність СК2 кінази з ІС50 - 18,8 мкМ та IC50 - 22,4 мкМ. Protein kinase CK2 (Casein Kinase 2) is a ubiquitous serine/threonine protein kinase involved in various cell signal transduction pathways. Thus, CK2 is a new perspective target for anticancer drugs. The receptor-based virtual screening of 2000 compounds from combinatorial library of 4H-4-chromenones has been carried out in search for CK2-inhibitors. 90 compounds have been chosen for biological testing based on the score values calculated by DOCK 4.0 software. It has been revealed, that 3-(4-chloro-3,5-dimethylphenoxy)-7-(4-methoxyphenylcarbonyloxy)-4-oxo-4H-chromene (12) and 7-(4-fluorophenylcarbonyloxy)-4-oxo-3-(4-phenylphenoxy)-4H-chromene (14) inhibit CK2 activity with IC50= 18.8 mM and IC50=22.4 mM, respectively.